Policy myopia as a source of policy failure: adaptation and policy learning under deep uncertainty. (17th January 2017) - Nair, Sreeja; Howlett, Michael
Abstract : A critical challenge policy-makers deal with in responding to problems concerns gaps and reliability issues with respect to the information they are using as well as the difficulties and risks associated with accurately anticipating the future. Failing to correctly identify the bounds and range of these uncertainties and assuming a greater level of certainty in the short-term than may exist in the long – 'policy myopia' – is a major cause of policy failure. This paper reviews the literature on uncertainty and its implications for policy-makers, especially aspects of policy adaptation and learning which can help avoid myopic responses.